Pengembangan Alat Permainan Edukatif Kartu Giling Huruf untuk Meningkatkan Kemampuan Membaca Anak Usia Dini 4-6 Tahun - Sri Harti; Nunuk Suryani; Deny Tri Ardianto (Teknodika, 2017)
Kartu Giling Huruf (KGH) as one of the learning media for reading needs to be developed, both in terms of shape, size, color, and material to be more interesting to children so that children will play this tool more often and more easily understand letters and vocabulary as contained in KGH. This research is intended to develop KGH as a medium for learning to read for early childhood 4-6 years old. The sampling procedure in this developmental research follows the ADDIE development model (analysis, design, development, implementation, and evaluation) which is carried out in Ar-Rohmah Kindergarten. The stages required observation time along with the development of KGH in semester 2, February - May in 2014/ 2015 academic year. Theresults of the effectiveness test and trial development results showed that the KGH developed is ready to be used and produced in a wider scope.